PENGARUH PENERAPAN INFORMASI AKUNTANSI MANAJEMEN TERHADAP KINERJA KOPERASI KREDIT FAMILIA KUPANG - Tomasui, Olivia; Amtiran, Paulina Yuritha; Ndoen, Wehelmina M (Universitas Nusa Cendana, 2022)
This study aims to determine the effect of the application of management accounting information which is focused on the frequency of routine reports, the frequency of non-routine reports and the quality of management accounting information on the performance of the Kupang Familia Credit Cooperative. The research method used is a quantitative research method. The population in this study were employees and members of the cooperative as many as 30 respondents. The results showed that partially the frequency of routine reports and the frequency of non-routine reports had a significant effect on the performance of cooperatives by having a negative relationship. And the quality of management accounting information has a significant effect on the performance of cooperatives with a positive relationship. Meanwhile, the variables of the frequency of routine reports, the frequency of non-routine reports and the quality of management accounting information simultaneously affect the performance of cooperatives. The results of the determination test show that the value of R square is 0.980 which shows the large percentage of the contribution of the independent variable (X) to the dependent variable (Y) of 98.0% and the remaining 2% is influenced by other variables not included in this study. Keywords: Frequency of Routine Reports, Frequency of Non-routine Reports, Quality of Management Accounting Information, Cooperative Performance